Towards AI-Powered Inclusive Education in the Gulf States and Yemen: A Reality Analysis and a Proposed Approach (The International Journal of Educational Sciences and Arts, 2025)
This study analyzes the use of artificial intelligence (AI) to support inclusive education in GCC countries and Yemen and proposes a practical framework to enhance this approach. Using a descriptive-analytical method with surveys, interviews, and document analysis, the findings reveal limited AI application and disparities in policies, infrastructure, and staff awareness. The study presents a proposed model to activate AI in inclusive education, aiming to promote more equitable and accessible learning environments.
Keywords: Inclusive Education; Artificial Intelligence Technologies; Children with Disabilities; Gulf Countries and Yemen